The Trends of â€œWomen In The Quranâ€ in The Study of Gender Verses (Barbara F Stowasser's Reinterpretation Study) - Cholidi, Muhammad Fiqih; Fadlulah, Safiya (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This paper aims to present the urgency of the reinterpretation of female figures narrated in the Qur'an. The debates that emerged in the contemporary era became social claims which had implications for grouping groups based on social perceptions obtained from the time. This paper then collects things related to Barbara F. Stowasser to answer her thoughts on women's work. Through the literatureâ€™s genre initiated by hers, this article analyzes the structuralization of social impact raised in different categories of interpretation. The results of this tracking prove that, although the debate regarding the story in the Qur'an has yet to be completed, it still provides relevance to the social construction that one wants to build on the status of women in society.